Empirical Study of the Impact of Financial Risk and Regulation on the Performance of Moroccan Banks - EL CHAREF , Fatima; EL BAKKOUCHI , Mounir; EL MORAJJI , Nora (Revue du contrôle, de la comptabilité et de l’audit, 2022)
Following several studies in the theoretical and financial literature, many factors characteristic of the banking system related to risk, banking regulation and macroeconomic conditions are used in this paper to study their influence on the performance of Moroccan banks. In detail, we used the cost of risk as a bank risk variable. In addition, the capitalization ratio, leverage ratio, and liquidity ratio have been introduced as capital structure and prudential regulation variables, while bank performance is approximated by the return on assets ROA, return on capital ROE, and the interest margin ratio RRMNI. Beyond the integration of bank-specific variables, we use some macroeconomic control variables, namely the inflation rate and the economic growth rate. We try to explain how risk and regulation affect performance and also this relationship can be linked to macroeconomic variation. This research concerns the 10 largest banks (AWB, Barid Bank, SGMB, CAM, BOA, BP, BMCI, CIH, CDM and CDG) over a period from 2010 to 2020. We have opted for the panel data analysis method with the generalized least squares method (GLS) to obtain robust and validated results. To do so, we described 3 econometric models conceptualized to answer our problem. At the end, these results have been subjected to in-depth analysis and discussion, while relating the role of risk and banking regulation in the financial and economic implications of the Moroccan banking and financial system.